2019
DOI: 10.5267/j.ijiec.2018.6.002
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate production planning: A literature review and future research directions

Abstract: Aggregate production planning (APP) is concerned with determining the optimum production and workforce levels for each period over the medium term planning horizon. It aims to set overall production levels for each product family to meet fluctuating demand in the near future. APP is one of the most critical areas of production planning systems. After the state-of-the-art summaries in 1992 by Nam and Logendran [ Nam, S. J., & Logendran, R. (1992). Aggregate production planning-a survey of models and methodologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 38 publications
0
59
0
2
Order By: Relevance
“…The authors have benefited from their decade-long experience of doing concentrated research on APP under uncertainty and their deep familiarity with APP literature to critically review and analyse a comprehensive set of relevant literature. Some of the major features of this literature survey which differentiates it from those conducted by Nam and Logendran (1992) and Cheraghalikhani, Khoshalhan and Mokhtari (2019) are as follows:…”
Section: The Need For Literature Survey On App Under Uncertaintymentioning
confidence: 99%
“…The authors have benefited from their decade-long experience of doing concentrated research on APP under uncertainty and their deep familiarity with APP literature to critically review and analyse a comprehensive set of relevant literature. Some of the major features of this literature survey which differentiates it from those conducted by Nam and Logendran (1992) and Cheraghalikhani, Khoshalhan and Mokhtari (2019) are as follows:…”
Section: The Need For Literature Survey On App Under Uncertaintymentioning
confidence: 99%
“…Aggregate production planning consists on moving the business plan in the medium-long term to the world of production, generating medium-long-term production planning, which is based on a forecast or estimate of the demand in that period, and based on productivity criteria, efficiency, pre-established and estimated capacity (Cheraghalikhani et al, 2019). Accordingly, the production aggregate planning deals with planning capacity needs and availability to meet market needs, planning the materials for its on-time reception, in the correct quantity needed for production.…”
Section: Aggregate Production Planningmentioning
confidence: 99%
“…For long time, it has been demonstrated that Variant B allows major benefits such as minimizing staffing fluctuations, reducing overheads or increasing production efficiency [4]- [6]. However, it has also been demonstrated that such a Variant is not trivial to be implemented in real context [7]- [9]. This research work focuses on this problem statement and attempts (i) to demonstrate the feasibility of using an aggregated model (Variant B) to support the AS&OP process and (ii) to discuss benefits and limits of following such an approach.…”
Section: Introductionmentioning
confidence: 99%